Effective Mathematics Instruction for Students With Moderate and Severe Disabilities: A Review of the Literature. (December 2019) - Bowman, Jessica A.; McDonnell, John; Ryan, Joanna H.; Fudge-Coleman, Olivia
Educational programs for students with moderate and severe disabilities (MSD) have undergone drastic changes since the mandate for access to the general curriculum was provided by Individuals With Disabilities Education Act. Since then, educators have struggled to find methods to use to promote optimal learning, including in the area of mathematics. The purpose of this systematic literature review was to provide an update on research related to teaching mathematics to students with MSD published from 2005 to 2017. Results from the included studies indicated that mathematics research has started to diversify in the skills that are being taught to this population. In addition to skills taught, current research has continued to inform the field on some promising methods that can be used to teach a broader range of mathematics skills. Emerging strategies that were identified included the use of concrete representations, anchored instruction, and instructional technology. Suggestions for future research are discussed.